The manual of detection [compact disc, unabridged] - Berry, Jedediah (HighBridge Audio, 2009)
Charles Unwin, a clerk in a detective agency, is promoted to the rank of detective after illustrious detective Travis Sivart goes missing and his boss is murdered. As Unwin mounts his search for the missing Sivart, he is soon framed for murder, pursued by goons and gunmen, and confounded by the infamous femme fatale Cleo Greenwood.